Highly flexible few-layer Ti3C2 MXene/cellulose nanofiber heat-spreader films with enhanced thermal conductivity. (23rd April 2020) - Song, Guichen; Kang, Ruiyang; Guo, Liangchao; Ali, Zulfiqar; Chen, Xiaoyong; Zhang, Zhenyu; Yan, Chao; Lin, Cheng-Te; Jiang, Nan; Yu, Jinhong
Abstract : Highly flexible MXene/cellulose nanofiber heat-spreader films with enhanced thermal conductivity were fabricated via simple vacuum assisted filtration. Abstract : MXenes, two-dimensional transition metal carbides, exhibit excellent properties in many fields such as energy storage. The first discovered, Ti3 C2, has been widely used in lithium ion batteries. However, thermal properties and delamination of few-layer MXenes have been insufficiently explored. In this work, few-layer Ti3 C2 nanosheets were prepared under ultra-high pressure and by low temperature exfoliation. Furthermore, a flexible cellulose nanofiber (CNF)/Ti3 C2 composite film was fabricated by simple vacuum-assisted filtration. The heat spreader of Ti3 C2 /CNF paper exhibits in-plane and out-of-plane thermal conductivities of 11.57 and 1.57 W m −1 K −1 with 50 wt% loading of filler, respectively. Moreover, the synthesized Ti3 C2 /CNF composite films presented outstanding flexibility because the films can be folded to any shape, which enables Ti3 C2 /CNF composite films to be potentially applied in flexible electronic devices for heat dissipation.